RELATIONSHIP BETWEEN ANTICARDIOLIPIN AND DIABETESMELLITUS PATIENTS TYPE 2 - Aboud, Rana S; Mohammad, Haider J; Ismaeel, May K (Al-Nahrain Journal of Science, 2018)
An Anticardiolipin antibody, oxidatively modified low-density lipoproteins is humoral factor that has been linked to vascular damage. To analyze their possible role in the complication in type 2 diabetes mellitus, we investigated (22) patients with diabetes mellitus type 2 of ages (35-68) years.The patients were also compared with (20) healthy individuals. The level of anticardiolipin antibody was measured by using Enzyme Linked Immuno Sorbent Assay test (ELISA),there was a highly significant elevation in IgM and IgG anticardiolipin concentration in patient with diabetic mellitus than in controls group (P < 0.001). The prevalence of IgM and IgG anticardiolipin antibody was (13.6% and 9.1%) respectively. There were highly significant differences between study groups than in control groups.The higher levels of anticardiolipin Abs of both type IgG and IgM suggests that these humoral factors might be involved in the pathogenesis and complications of type 2 diabetes mellitus.